Balance of Payments Pressures on the Exchange Rate - Drahozalová, Anna; Janíčko, Martin, 1983-; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2022)
This paper contributes to the existing literature on exchange rate modelling by developing a new proxy for foreign exchange market imbalances. By utilizing the monetary presentation of the Balance of Payments we create a measure of net external monetary flows and study its relationship with the exchange rate. To account for both fixed and floating exchange rate regimes we rely on a version of the exchange market pressure (EMP) index. A structural vector autoregression model provides evidence of a causal relationship from net external monetary flows to the EMP index. We find that a positive orthogonal shock to net external monetary flows causes the exchange rate to appreciate already in the short term with the effect peaking three months after the initial shock.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses